IMPLICATIONS OF THE PRINCIPLE OF NON-DISCRIMINATION IN THE INDONESIA-EUROPEAN UNION COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT ON GOVERNMENT PROCUREMENT CHAPTER TOWARD REGULATIONS OF DOMESTIC PRODUCT USE IN INDONESIA - Syukri, Syukri; Amalia, Prita (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2020)
This article aims to explain the differences between regulations on the use of domestic product in Indonesia and the principle of non-discrimination in Indonesia-European Union Comprehensive Economic Partnership Agreement (I-EU CEPA) on Government Procurement Chapter and the legal consequences for domestic regulations in Indonesia. The research method used is a normative juridical method with exploratory specifications. The results of this study indicate that the principle of non-discrimination, which consists of most favored-nation treatment and national treatment in the I-EU CEPA on Government Procurement Chapter, differs from regulations in Indonesia because the use of domestic product is mandatory in the government procurement and discriminatory against foreign suppliers. The difference in these provisions has implications, namely if Indonesia and the European Union agree to the I-EU CEPA, they must adjust the regulations for the use of domestic product in accordance with the principle of non-discrimination in the I-EU CEPA or World Trade Organization Agreement on Government Procurement (WTO GPA) or ratify the I-EU CEPA in the form of a Law and its enforcement is lex specialis and it is necessary to make adjustments to the implementing regulations by giving time after entry into force. In addition, Indonesia does not have the obligation to provide equal treatment to third countries because the I-EU CEPA is a bilateral agreement and Indonesia is not yet bound by a multilateral agreement, namely the WTO GPA. In addition, if Indonesia and the European Union agree to an I-EU CEPA, the Indonesian side cannot cancel it on the grounds that it violates the provisions of national law.